COMMUNICATING ACROSS DISCIPLINES AND CONTEXTUAL DIVERSITY: THE EXAMPE OF RUSSIAN COMMUNICATION ASSOCIATION - Rozina, Irina; Tuzlukova, Victoria (European Scientific Journal, ESJ, 2014)
This paper presents a pilot study aimed at streamlining and systematizing information on the development of the communicative trends in Russia. To achieve this goal the authors utilize the results of the examination of the most significant long-term projects of the Russian Communication Association (RCA) in relation to their dynamics and quantitative indicators across disciplines and contextual diversity of its members’ profiles, activities and partnerships with academic schools, other professional organizations, specialized departments, faculties and universities in Russia and worldwide. The data sources included the archives of documents and publications, including the archive on the RCA public website (russcomm.ru), journals, monographs and books collected during the implementation of the association’s book project, and internet resources. In addition, the examination was supported by the results of the survey (open-ended questions) of a representative sample of the RCA members and participants of the RCA’s social groups, and by the results of direct observations of the behavior of the participants of the scientific communication. These observations mostly focused on the behavior of the participants during preparatory and implementation stages of the RCA’s most significant events and in events of interpersonal communication: e-mail correspondence, mailing lists, answers and comments to messages in social groups, etc. The results of the examination can provide insights for further development of studies in the domain of theory and practice of communication.